Gender Differences and Programming Environments Across Programming Populations - Burnett, Margaret M.; Fleming, Scott D.; Iqbal, Shamsi; Rajaram, Vidya; Farooq, Umer; Czerwinski, Mary; Venolia, Gina (ACM ESEM, 2010)
Although there has been significant research into gender regarding educational and workplace practices, there has been little investigation of gender differences pertaining to problem solving with programming tools and environments. As a result, there is little evidence as to what role gender plays in programming tools—and what little evidence there is has involved mainly novice and enduser programmers in academic studies. This paper therefore investigates how widespread such phenomena are in industrial programming situations, considering three disparate programming populations involving almost 3000 people and three different programming platforms in industry. To accomplish this, we analyzed four industry “legacy” studies from a gender perspective, triangulating results against each other and against a new fifth study, also in industry. We investigated gender differences in software feature usage and in tinkering/exploring software features. Furthermore, we examined how such differences tied to confidence. Our results showed significant gender differences in all three factors—across all populations and platforms.